1983
DOI: 10.1111/j.1365-2621.1983.tb10778.x
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Index of the Dispersed Phase in Oil‐in‐Water Emulsions: Its Dependence on Droplet Size and Aging

Abstract: A simple method of determining the refractive index of the dispersed phase was applied on different gum-stabilized oil-in-water emulsions, in which this refractive index is taken to be equal to that of the continuous phase at (extrapolated) zero optical density point. Refractive indices of dispersed phases were usually lower than those of the oil part alone. In dilute emulsions, the refractive index of the dispersed phase increased with time, while optical density of emulsion decreased. In aged concentrated em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…1. Previous studies [16,18,22] have also reported the decrease in the turbidity of emulsions over the time. The lower degree of turbidity loss rate indicates more cloud stability in oil-inwater emulsions [16].…”
Section: Turbidity Loss Rate (Cloud Stability)mentioning
confidence: 84%
See 1 more Smart Citation
“…1. Previous studies [16,18,22] have also reported the decrease in the turbidity of emulsions over the time. The lower degree of turbidity loss rate indicates more cloud stability in oil-inwater emulsions [16].…”
Section: Turbidity Loss Rate (Cloud Stability)mentioning
confidence: 84%
“…As explained further in Section 3.3, all of the emulsions studied here showed an increase in their average droplet diameters over 42 days of storage. Ray et al [22] also reported that decrease in the turbidity of such emulsions in their diluted forms could be due to an increase in the average droplet size (aggregation of oil droplets) via the instability phenomena throughout the storage time. According to Dluzewska et al [18], the decrease in the turbidity of diluted emulsions could result in the loss of polysaccharide molecules (desorption) for external layers of film formed on the interfacial surface leading to a change in the refractive index of dispersed phase.…”
Section: Turbidity Loss Rate (Cloud Stability)mentioning
confidence: 96%
“…Materials and their sources for emulsions have been given elsewhere (Ray et al, 1983). Sodium chloride (A.C.S.…”
Section: Methodsmentioning
confidence: 99%
“…Stability index determination. The original emulsions were diluted 1500-fold with water and absorbances were determined at 700 and 400 nm against water (Ray et al, 1983). The ratio of absorbances at 700 and 400 nm will be called stability index (Horie et al, 1978;Kaufman and Garti, 1981).…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation